Is supplementation justified to compensate pastoral calves for milk restriction? - Coppock, D. Layne; Sovani, S. (1999)
Competition for milk between calves and pastoral herders may reduce weaning weights, retard growth, and delay puberty in cattle. Calf supplementation could over-ride such effects and improve pastoral economies. To examine these issues in semiarid Ethiopia, 266 Boran calves (Bos indicus) were used in a 2x3 plus 1 factorial design contrasting graded levels of supplemental alfalfa hay (i.e., Medicago sativa L. with mean intakes of 0,344, and 557 g head -1 day on a DM basis) and supplemental water (i.e., with mean intakes of 0 and 3.8 liters head -1 day). The trial was repeated for animals born in 2 consecutive years. Treatments occurred over a background of simulated traditional management in which calves had limited access to grazing and water and were allowed to suckle about two-thirds of their dams daily milk yield. Traditionally managed controls received no supplements while other (positive) controls received no supplements but had greater access to milk. After 10 months of treatment calves were weaned and monitored. Supplementation with the high level of hay plus water markedly enhanced (P<0.01) all productive features of calves at weaning compared to traditionally managed controls, and was an effective substitute for milk forgone in both years. Despite high variability in milk intake, access to supplements, and weaned body size as calves, all male cattle converged in liveweight and other productive features by 3.5 years of age, largely due to compensatory growth of traditionally managed controls. Heifers also converged in various attributes at maturity, but those which had received hay plus extra water as calves still conceived 2.6 to 4.3 months earlier (P<0.05) than traditionally managed controls. We concluded that supplementation with hay and water can indeed compensate a young calf for typical levels of milk restriction here. Carry-over effects, however, were insufficent to justify large investments in supplementation considering the high inherent risks of production and traditions of marketing mature animals.